The Mediating Role of Job Satisfaction and Organizational Commitment on Employee Performance - Ruhdiat, Rudi; Wibisono, Chablullah; Puspita, Nola (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Employee performance is vital for organizational success, driven by effective leadership, work discipline, and communication, with job satisfaction and organizational commitment shaping these relationships. This study aims to explore how leadership, discipline, and communication shape employee performance by examining employees’ lived experiences and perceptions, with particular attention to the role of job satisfaction and organizational commitment within Indonesian organizations. The research develop a comprehensive model integrating these factors to enhance performance. Using a qualitative approach, the study conducts a literature review, analyzing journal articles, conference proceedings, and textbooks through thematic content analysis. Findings confirm that transformational leadership strongly inspires higher performance, work discipline ensures accountability and efficiency, and clear communication fosters trust and collaboration, all significantly boosting employee performance. Job satisfaction powerfully mediates these effects by enhancing motivation, while organizational commitment strengthens the satisfaction–performance link, particularly in Indonesia’s collectivist culture. The study concludes that organizations in Indonesia can improve performance by adopting transformational leadership, fair disciplinary systems, and transparent communication, with job satisfaction and commitment as critical levers. These insights provide practical strategies for Indonesian organizations and lay a foundation for future empirical research to validate the model in specific industries like healthcare and technology.